Shear Behavior of Strengthened Ferrocement RC Beams by Steel Wire Mesh - Sarah H. Hameed; Abdulkhaliq A. Jaafer (Civil Engineering Journal, 2022)
This paper investigates the possibility of strengthening a ferrocement RC beam with steel wire mesh under static loading. This experimental study included testing ten normal and high-strength concrete specimens made with ferrocement. The main parameters were the steel wire mesh layers 4, 8, and 10 in addition to the compressive strength and shear to span to depth ratio of 1.8 and 2.5. The cracking load, ultimate load, deflections, initial stiffness, energy absorption, diagonal and compressive strains, and crack pattern and failure modes of such beams were discussed. The outcomes exhibited that the beams behave linearly until they reach about 21.5% of the ultimate strength for the normal concrete beam and 23.2% for the high-strength concrete beam. The steel wire mesh presence affected the ultimate strength of the concrete beam, which increased the cracking load by an average of 15.5% for the high-strength RC beam and by 24.2% for normal-strength RC ones. The ultimate load was increased by an average of 40% for the high-strength strengthened beams and with less percentage for the normal ones, which was 31%. The  ratio affected the ultimate load-carrying capacity and maximum displacement directly, which increase  led to a decrease in the ultimate load-carrying capacity. The strengthening by steel wire mesh enhanced the initial stiffness, ductility, and energy absorption. Doi: 10.28991/CEJ-2022-08-05-04 Full Text: PDF